Approximation by de la Vallée-Poussin operators on the classes of functions locally summable on the real axis - Rukasov, V. I.; Chaichenko, S. O. (Ukrains’kyi Matematychnyi Zhurnal, 2010)
For the least upper bounds of deviations of the de la Vallée-Poussin operators on the classes L^ψ_β of rapidly vanishing functions ψ in the metric of the spaces L_p, 1 ≤ p ≤ ∞, we establish upper estimates that are exact on some subsets of functions from L_p.